2020
DOI: 10.1039/c9ra10731b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the non-hydrolytic sol–gel process of tellurite glass films to attain a high transmission

Abstract: This work develops a high-transparency amorphous film with a wide transmission window and high refractive index, which can potentially meet the strong demand of integrating functional nanoparticles for the next-generation hybrid optoelectronic films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Sodium zinc tellurite sol–gel glass films were explored in relation with the mechanism of the TeO 2 reduction to metallic-Te [ 7 ]. It was demonstrated that the formation of metallic-Te is responsible for the decrease of the optical transmission in the Vis domain.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium zinc tellurite sol–gel glass films were explored in relation with the mechanism of the TeO 2 reduction to metallic-Te [ 7 ]. It was demonstrated that the formation of metallic-Te is responsible for the decrease of the optical transmission in the Vis domain.…”
Section: Introductionmentioning
confidence: 99%